2018
DOI: 10.1002/pola.29297
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Crosslinkable and Chemically Modifiable Aromatic Polyesters Possessing Pendant Propargyloxy Groups

Abstract: New aromatic (co)polyesters containing pendant propargyloxy groups were synthesized by phase transfer‐catalyzed interfacial polycondensation of 5‐(propargyloxy)isophthaloyl chloride (P‐IPC) and various compositions of P‐IPC and isophthaloyl chloride with bisphenol A. FTIR and NMR spectroscopic data, respectively, revealed successful incorporation of pendant propargyloxy groups into (co)polyesters and formation of (co)polyesters with desired compositions. (Co)polyesters exhibited good solubility in common organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…As a type of high-performance special engineering plastic, aromatic polyesters have been widely used in sectors such as industrial production, medical and healthcare, and machinery manufacturing, as well as in daily life. [1][2][3][4][5] A representative aromatic polyester is the commercialized bisphenol-A (BPA) polyarylate. Owing to their highly symmetrical structure, aromatic polyesters exhibit a high molecular chain rigidity, high thermal stability, and excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a type of high-performance special engineering plastic, aromatic polyesters have been widely used in sectors such as industrial production, medical and healthcare, and machinery manufacturing, as well as in daily life. [1][2][3][4][5] A representative aromatic polyester is the commercialized bisphenol-A (BPA) polyarylate. Owing to their highly symmetrical structure, aromatic polyesters exhibit a high molecular chain rigidity, high thermal stability, and excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a type of high‐performance special engineering plastic, aromatic polyesters have been widely used in sectors such as industrial production, medical and healthcare, and machinery manufacturing, as well as in daily life 1–5 . A representative aromatic polyester is the commercialized bisphenol‐A (BPA) polyarylate.…”
Section: Introductionmentioning
confidence: 99%
“…The XRD diffraction patterns of the co‐PARs demonstrated a wide halo at 2θ = 10–20°, indicating its amorphous nature. Apparently, the insertion of sulfur‐containing bulky groups hindered the crystallization of the polyarylate and reduced the regularity of the molecular chain, which leads to the formation of amorphous co‐PARs 26–28 …”
Section: Resultsmentioning
confidence: 99%
“…17 Relatively new aromatic copolyesters synthesized from 5-(propargyloxy) isophthaloyl chloride and bisphenol A have displayed 10% weight loss around 400°C validating their superior thermal stability. 18 Analogy between polyesters derived from Terephthaloyl dichloride and Isophthaloyl dichloride along with hindered Biphenols and bulky substituent bearing Hydroquinones has revealed that polyesters obtained from Isophthaloyl dichloride exhibit better solubility and lower glass transition temperatures. 19 High molecular weight crystalline aromatic copolyesters obtained from bisphenols containing pendant, Quinoxaline moiety by polymerization with Isophthaloyl chloride are reported to be thermally stable.…”
Section: Introductionmentioning
confidence: 99%